Long Term Investor Relationships and Corporate Financial Disclosure Practices (gjstudies, 2017)
This research investigates the underexplored nexus between the temporal orientation of investor relationships and the qualitative dimensions of corporate financialdisclosure. Departing from conventional studies that treat investors as a homogeneousgroup or focus primarily on institutional ownership percentages, we propose a novelconceptual framework that categorizes investor relationships along a continuum fromtransactional to transformational, based on investment horizon, engagement depth,and informational symbiosis. We hypothesize that firms with a preponderance of longterm, relationally-embedded investors (termed ’transformational investors’) will exhibitfinancial disclosure practices characterized by greater forward-looking orientation, enhanced transparency regarding strategic trade-offs and intangible assets, and a highertolerance for the disclosure of interim negative performance, compared to firms dominated by short-term, transactional investors. To test these propositions, we develop anoriginal, multi-method methodology. First, we construct a proprietary ’Investor Relationship Horizon Index’ (IRHI) using a combination of machine learning text analysisof investor communication transcripts, analysis of shareholder registry turnover, and asurvey of corporate investor relations officers. Second, we employ a novel ’DisclosureQuality Depth’ (DQD) metric that moves beyond disclosure quantity to assess thestrategic usefulness, contextual richness, and temporal orientation of financial reportsand voluntary disclosures. Applying this framework to a longitudinal dataset of SP500 firms from 1998 to 2004, our results reveal a statistically significant and economically meaningful positive association between a firm’s IRHI score and its DQD metric.Furthermore, we find that this relationship is moderated by industry volatility and mediated by reduced managerial myopia. The study contributes a new theoretical lens forunderstanding disclosure behavior, grounded in relational contracting and stewardshiptheory, and offers practical implications for regulators advocating for long-termism incapital markets and for corporate boards structuring their investor base.